Do Boards Determine Integrated Reporting in Nigerian Listed Oil and Gas Firms? - Teryima Orshi; Kabiru Isa Dandago; Rehanet Isa (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose: Integrated reporting is a process founded on integrated thinking, with the aim of issuing periodic integrated reports by firms about value creation over time. This study investigates the effect of board attributes (independence, diligence, and size) on the quality of integrated reporting of Nigerian listed oil and gas firms. Design/Methodology: Panel data are obtained from annual reports of a purposive sample of 10 out of the 12 listed Oil and Gas firms in Nigeria from 2013 to 2017. These are analyzed using multiple regression techniques, via STATA 13.0 software. Results: Based on the analysis conducted, findings show that the board independence and board size have a significant and positive effect, while board diligence has an insignificant and positive effect on the quality of integrated reporting, proxied by integrated reporting disclosure score (IRDSCORE). This outcome implies that having the optimum mix of members on the board influences the extent of integrated disclosures of listed oil and gas firms in Nigeria. Practical Implications: Global corporate reporting is currently driving towards integrated thinking, incorporating financial, governance, social and environmental issues to promote long-term value creation. As a third world nation, the adoption of integrated reports is voluntary in Nigeria. However, considering the information needs of all stakeholders and appointing qualified persons on the board by shareholders, and formulating enabling policies in this direction by regulatory agencies would drive corporate reporting to be more integrative to drive long-term value maximization.